New method to develop High temperature constitutive model of metal based on the Arrhenius-type model. (September 2020) - Wang, Haoran; Zhang, Zhiyuan; Zhai, Ruixue; Ma, Rui; Zhao, Jun
Graphical abstract: Highlights: The new method of solving material constants is proposed. The method is proposed to obtain the initial guess of the new method. The offset error is introduced to reduce computational cost. The new method reduces AARE-value of the predicted value from −5.6599% to 0.0533%. Abstract: The isothermal compressions of Mg-Gd-Y-Zn-Zr alloy in a temperature range of 653–773 K and strain rate range of 0.001-1 s −1 were conducted. The Arrhenius-type equation is widely applied to describe the complex behavior of the flow stress at elevated temperatures. Linear regression is the most common method to solve material constants of the Arrhenius-type equation in previous research. In prevent study, a new method is proposed to solve material constants. The new method combines an iterative method with regression analysis, and it transforms the Arrhenius-type equation into a system of equations of two equations. Moreover, to improving convergence speed, we introduce an offset error into one equation in the system of equations and propose methods to determine the initial guess. A comparative study has been made between the new method and the regression method. The result shows compared with the regression method, the new method improves the prediction accuracy of the Arrhenius-type equation, and it decreases the number of regression operations when the same average absolute relative error (AARE) value is used as a criterion.